Traduire l'expression «soi-disant» en polonais: le cas des copies d'étudiants - Dutka-Mańkowska, Anna (Wydawnictwo Naukowe UAM, 2003)
Students' translations into Polish of the French expression soi disant (found in the "Frantext" programme) are considered on two Ievels: that of linguistic means used (modalisers, antonymous modality, apparent reported speech, verb expressions of the type: vouloir/paraitre/passer pour and ways of quoting another discourse (possibility of using explicite/implicite). The semantic and contrastive approach appears to be useful in the description of Polish words (e.g. niejako), particularly difficult from the point of view of the theory of combinations.
Translation of the expression soi-disant into Polish: a case of students' calques
Keywords: Expression "soi-disant"; Translation